PEMANFAATAN SUMBER BELAJAR PEMBELAJARAN JARAK JAUH (PJJ) DI SMK BINUSTA CIPONDOH KOTA TANGGERANG - Miftah Al-Mahbub Miftah Al-Mahbub; Alfan Noviansyah; Suhendang Suhendang; Rahmawati Rahmawati (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
Learning resources are everything in the form of objects and people that can support learning so that it includes all possible sources that can be utilized by the faculty in order to study the behavior that occurs. factors that ecourage students and teachers in choosing and utilizing various distance learning learning resources, namely: (1) Internal is the awareness, motivation, interest, ability, and comfort in the user, and (2) External is the availability of learning resources, variety of sources learning, quantity of learning resources, quality of learning resources, ease of access to learning resources, forms and types of learning resources, learning, space, human resources, as well as traditions and systems of applicable educational institutions. The tendency to use various learning resources in educational units is influenced by two main factors, namely internal factors and external factors. Dominant internal factors affect the user's own awareness, passion, interest, ability, and comfort. In terms of external factors that affect the availability of varied learning, the quantity of learning resources, easy access to learning resources, learning, space, human resources, as well as traditions and systems that apply in educational institutions, especially at SMK Binusta Cpondoh Tangerang City.